PENGARUH PERSEPSI KUALITAS STASIUN MANGGARAI PADA JAM PULANG KERJA - Fitri Anggraeni; Dwi Wahyu Salsabila, Dewi Setianingsih, Siti Sahara (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The train is a means of land transportation that is most in demand by the public to connect the central city with the surrounding cities which must be balanced with facilities in the form of adequate stations. The purpose of this study was to see the public's perception of the quality of the Manggarai Station during work hours. The research began by identifying public perceptions of Manggarai Station using the survey method by filling out questionnaires distributed through social media which resulted in statements that Manggarai Station was good enough in service and needed to improve facilities, security and the train fleet so as not to make passengers have to wait long to get their trains. the appropriate route to the destination